Nilai-Nilai Teologis tentang Tidak Ada yang Berkelebihan dan Tidak Ada yang Berkekurangan Berdasarkan 2 Kor. 8:13-15 dan Relevansinya bagi Praktek Gereja Masa Kini - Lieberth, Ricard; Hermanto, Yanto Paulus (Jurnal Teologi (JUTEOLOG), 2025)
This study examines the principle of equality in the body of Christ based on 2 Corinthians 8:13–15, particularly the idea that “no one has too little and no one has too much.” The issue is significant because socio-economic injustice and inequality remain real challenges for the contemporary church. The purpose of this research is to explore the Christian ethical meaning of the text and its implications for the praxis of today’s church. The method employed is a theological literature review and biblical exegesis with an applied ethics approach. The findings highlight a novelty that Paul’s principle is not merely a charitable teaching, but a paradigm of equity rooted in the love of Christ. This discovery is important as it reaffirms the church’s calling to embody tangible solidarity that fosters equality within the body of Christ and the wider society.